Teaching Vocabulary Using Audiovisual Aids at the First Grade Students of SDN 2 Sawahan In 2014/2015 Academic Year: A Classroom Action Research - Utami O. F, Dian (2016)
The teaching English vocabulary in Elementary School was different from teaching in Junior High School or Senior High School. The teacher needs some audiovisual and visual aids to catch the students' attention. This study is aimed at describing the procedures of teaching vocabulary using audiovisual aids, its result to the students and for explaining the advantages and disadvantages of teaching English using audiovisual aids. The teaching learning process was conducted by using Classroom Action Research (CAR). The result of teaching English vocabulary using audiovisual aids for the first grade students of SDN 2 Sawahan improved. The entire student showed with their participation in learning English, their score was also better and the class became happy and fun. The advantages of teaching English using audiovisual aids are: 1) the teacher could control the classroom situation easily; 2) the teacher could teach the students easily; 3) the students could be interested in learning English; 4) the students could know how to spell the words correctly; 5) the teaching-learning process became funny and happy, and 6) the students became active. The disadvantages of teaching English vocabulary using audiovisual aids are: 1) the teacher took more time to prepare the projector; 2) the teacher could not teach using audiovisual everyday; 3) the teaching-leaning process could not run well if the electrical power went down, and 4) the teaching-learning could not run well if the teacher didn't understand how to use the audiovisual aids.